Evaluation of Islamic Religious Education Learning through Diagnostic Assessment: Opportunities and Challenges - Khaira Ummah; M. Luthfi Al-Fatih; Remiswal Remiswal; Khadijah Khadijah (The Future of Education Journal, 2026)
Diagnostic assessment plays a crucial role as it addresses not only cognitive aspects but also encompasses affective and spiritual dimensions. This study aims to examine the opportunities and challenges associated with implementing diagnostic assessment in Islamic Religious Education (PAI) instruction. Employing a descriptive-evaluative qualitative approach, the study combines a literature review with interviews involving PAI teachers and school principals. The findings indicate that diagnostic assessment offers opportunities for teachers to map students' prior knowledge, support differentiated instruction, and devise teaching strategies better aligned with learners' needs. Furthermore, it serves as a means to gain a more holistic understanding of students' development regarding knowledge, attitudes, and learning readiness. However, implementation faces several challenges, including teachers' limited understanding of the concepts and the utilization of assessment results, the lack of optimal instruments for measuring affective and spiritual aspects, time constraints, and inconsistent institutional support. Therefore, enhancing teacher competence, developing more comprehensive instruments, and ensuring sustained school support are essential for the effective implementation of diagnostic assessment in PAI instruction.